2011
DOI: 10.1108/00483481111169634
|View full text |Cite
|
Sign up to set email alerts
|

Organizational attractiveness and prospective applicants' intentions to apply

Abstract: PurposeThis paper aims to clarify the process that leads prospective applicants to apply for a job vacancy when one is being evaluated. It proposes that prospective applicants evaluate a job vacancy based on the characteristics of the job and the organizational attributes. This will determine organizational attractiveness perception, and will result in the intention to apply for a job vacancy.Design/methodology/approachAn adapted employment ad that described a job and an organization were presented to 51 marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
137
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 58 publications
(89 reference statements)
10
137
0
9
Order By: Relevance
“…The studies that were found only mention the person-organization fit. One of the perspectives followed in these studies supports the importance of the worker's expectations when in search of a job (Cabral-Cardoso, 2001;Delgado, 2011;Gomes & Neves, 2011). In this sense, the person-organization fit is provided by the perception of values and culture, but a socialization process for the worker still has not occurred, since the worker still is not an active element of the organizational culture.…”
Section: Value Congruence and Work Stress In The Portuguese Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that were found only mention the person-organization fit. One of the perspectives followed in these studies supports the importance of the worker's expectations when in search of a job (Cabral-Cardoso, 2001;Delgado, 2011;Gomes & Neves, 2011). In this sense, the person-organization fit is provided by the perception of values and culture, but a socialization process for the worker still has not occurred, since the worker still is not an active element of the organizational culture.…”
Section: Value Congruence and Work Stress In The Portuguese Contextmentioning
confidence: 99%
“…In the context of Portuguese research, studies about work stress and organization values have considered the two as independent variables and only recently value congruence and its influence at the organizational level have been considered (Cabral-Cardoso, 2001;Gomes & Neves, 2011;Morais, 2011;Pérez-Nordtvedt, Payne, Short, & Kedia, 2008;Vicente, Rebelo, & Agostinho, 2011). An investigation in a Portuguese organization conducted by Morais, Ramos, and Jordão (2012) identified the presence of significant relationships between work stress and value congruence, establishing that as value congruence increases, labor stress decreases.…”
mentioning
confidence: 99%
“…Bazı çalışmalar ise örgütsel çekiciliğin iş özellikleri ile ilişkili olduğunu göstermiştir (örneğin, Gomes & Neves, 2011;Hannon, 1996;Nadler et al, 2010). Hannon (1996), çok sayıda çalı-şanı olan örgütlerin işgücü büyüklüğü aracılığıyla çekici olarak algılandıklarını rapor etmiştir.…”
Section: Introductionunclassified
“…Thomas ve Wise (1999) adayların iş özellikleri yerine örgüt özel-liklerini daha çok dikkate aldığını öne sürmüştür. Bu bağlamda, örgüt çalışanlarının dış imajının (Tsai & Yang, 2010), ağızdan ağı-za yayılan pozitif yöndeki reklamın (van Hoye & Lievens, 2005) ve kurum imajının (Güler, 2015) adayların örgütün çekiciliğine ilişkin algılarını etkileyerek işe başvurma niyetlerinde belirleyici olduğu saptanmıştır (Gomes & Neves, 2011;Jiang & Iles, 2011).…”
Section: Introductionunclassified
“…: Wright & Snell, 2005;Ehnert, 2009), such as, for instance, the ability to: act efficiently towards the problem of attracting highly qualified and talented HR (eg. : Gomes & Neves, 2011); develop training programs carrying high transfer abilities to work locations (eg. : Carbery & Garavan, 2005).…”
Section: Human Resource Managementand Market Pressures In Perspectivementioning
confidence: 99%